Urgency of Money Laundering Crime Policy Reform in the Implementation of Digital Rupiah in Indonesia - Agung Imam Santoso; Faisal Santiago (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The development of financial technology, especially with the introduction of the digital rupiah, presents new challenges in the supervision and prevention of money laundering (TPPU) in Indonesia. Although existing regulations are sufficient to regulate conventional transactions, these regulations are not fully prepared to anticipate potential money laundering risks related to digital transactions. This study identifies shortcomings in existing TPPU policies, including limited supervisory infrastructure, lack of regulations for cross-border transactions, and challenges in verifying identity in digital transactions. More adaptive policy reforms and comprehensive regulatory updates are needed to address these challenges. Applying advanced technology, strengthening coordination between related institutions, and public education is key to creating a safe and trusted financial ecosystem in dealing with financial technology-based transactions, including Rupiah Digital.